A mixed methods investigation of newly diagnosed prostate cancer patients' decision-making about treatment - CRAIG, AGNELLA (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2019)
Background: The incidence of prostate continues to increase but due to the management strategies available, the mortality rates are dropping. In Ireland, more than 3,400 men are diagnosed with prostate cancer annually. A number of management strategies are available to patients and include: active surveillance, watchful wait, surgery, brachytherapy, external beam radiotherapy, and hormone therapy. Patients, expected to actively participate in decision-making, must decide the strategy they will follow. As each option is associated with distinct adverse effects, making a treatment decision can be difficult, with decision conflict and decision regret reported in prostate cancer survivors. Little is known about the psychological processes prostate cancer patients undergo to arrive at this decision. Some factors that may influence decision-making, identified within the empirical literature, include; sociodemographic factors, knowledge, health literacy, self- efficacy, and [perceived] social support. Purpose: The overarching research questions considered in this research were: 1.What information do prostate cancer survivors think those diagnosed with prostate cancer need in order to make a treatment decision? 2.What factors are associated with decision conflict at the time of decision-making? 3.How do men with prostate cancer describe their decision-making process about their treatment options? Methods: A mixed methods sequential exploratory approach within a paradigm of pragmatism was used to address the three research questions. Specifically, the nominal group technique, a structured form of focus group was used in study 1 (n = 7) to address question 1. Using a survey, cross-sectional data from a convenience sample of prostate cancer patients was obtained in study 2 (n = 68) to test the conceptual framework, derived from the current literature. Semi-structured interviews were used in study 3 (n = 14), to explore how men describe the decision-making process, having just made their decision. Results: The results from the three studies were: Study 1: A list of 20 items was generated and ranked by 7 prostate cancer survivors; the item with top priority for this group was the "urgency of the condition, timeframe to make a decision". Study 2: Higher levels of health literacy and higher levels of self-efficacy were both independently associated with lower levels of decision conflict; and self-efficacy moderated the relationship between health literacy and decision conflict, when controlling for age, relationship status, perceived social support and knowledge of prostate cancer: i.e. higher levels of decision conflict were seen in men with low levels of health literacy and low self-efficacy in comparison to men with low health literacy but high self-efficacy. Perceived social support from friends was significantly associated with the decision conflict support subscale; those with high perceived social support from friends had better scores on the support subscale. Knowledge of treatment side effects was significantly associated with the decision conflict uncertainty subscale; as knowledge of the side effects associated with each treatment increased, uncertainty about decision-making increased. Study 3: Participants actively participate in decision-making but seem uninformed as to the specific consequences of their choice. Once survival is considered to be equal, beliefs and attitudes about surgery, either positive or negative, seemed to be the underlying basis for the decision. From the descriptions provided by the participants, patients seem to make a quick or rash decision based on a System 1 processing approach guided by heuristics and biases, rather than a rationalised, analytical System 2 process. Medical experts, family and friends and biases are utilised by patients to facilitate a justification of the decision. Conclusion: Prostate cancer patients are active participants in decision-making about treatment, make quick decisions about treatment, and experience low levels of decision conflict. However, the decisions are uninformed. Given the impact of treatment on quality of life, decision-making should be slowed down so that patients can incorporate their values and priorities into their decision-making. Adopting a shared decision-making approach in the clinical setting can facilitate patient- centred care.
APPROVED
Keywords: Health literacy; Decision-making; Prostate Cancer; Cancer treatment; Informed decision-making